Effect of roof ventilation on cooling performance of a building - Lio, Gillan Siang Kwang (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study is to show the effectiveness of roof ventilation on cooling performance of a building. The function and design of a roof is important because it is constantly exposed to the sun’s radiation throughout the day. Improper removal of heat on the roof will cause heat transfer to the inner building resulting in thermal discomfort to the occupants. Roof ventilation is one of the best ways to help in removal of heat. There are different types of roof ventilation used which are wind turbine ventilation, soffit ventilation, ridge ventilation and gable ventilation. EnergyPlus software was used as simulation to analyze the effectiveness of different types of roof ventilation. Before using the EnergyPlus for simulation, validation work was done to show the accuracy of the software. The validation work was done by comparing actual data collected on site to simulated data using EnergyPlus software. The data compared is the temperature. The deviation showed a range of 2% to 15%. After the validation work, the simulation of different types of roof ventilation was done. The simulation was done by comparing different types of roof ventilation with an unvented building to show whether there are improvement in terms of temperature. The result showed that wind turbine ventilation has the least improvement while soffit ventilation gave the best improvement by lowering the temperature of the building. Overall the result showed that roof ventilation can help in improving the cooling performance of a building.